Penerapan Terapi Relaksasi Benson Terhadap Penurunan Tekanan Darah dengan Hipertensi - Syahrani Syahrani; Rinawati Br Tarigan (STIKES Columbia Asia Medan, 2024)
Hypertension is a condition where a person experiences an increase in blood pressure above normal which can lead to an increase in mordibity and mortality rates. One of the nonpharmacological therapies that has been widely proven to reduce blood pressure is Benson relaxation. The design of this scientific paper uses a case study design of one patient subject in the Medan Sunggal Health Center work area. Data collection instruments used sphygnomanometer, stethoscope and observation sheet. The implementation of the application of benson relaxation is done by checking blood pressure before and after doing benson relaxation therapy, therapy is done once a day for 7 days with a duration of 10 minutes. After the application of benson relaxation therapy on Mrs.A, it was found that there was a decrease in blood pressure in Mrs.A with systolic results of 150 mmHg to 140 mmHg and diastolic 90 mmHg to 85 mmHg Benson relaxation therapy performed for 7 days on Mrs.A had an effect on lowering blood pressure. With this it is found that blood pressure decreases and relieves pain.